Classroom interaction and language learning among boys in coed and single-sex contexts - Rojas Alfaro, Roberto Enrique (2011)
This paper will address the differences and similarities in EFL interactive patterns of boys' learning in gender specific learning environments. The presentation will explore the findings of observational research conducted in coeducational and single-sex classrooms in two secondary schools in Costa Rica, namely Yorkin and New Hope schools. Data collection included class observation, interviews, surveys, questionnaires, photo ethnography and artifacts. The results revealed that boys in both contexts actually learn and behave similarly regardless of the gender specific learning environment in which they were immersed. They evidenced preference for kinesthetic, cognitive learning styles and task-oriented learning. Besides suggesting the need for school changes, the sudy brings out implications for teachers to adapt teaching strategies to acommodate their boys' learning styles.